Analisis Efisiensi pada Lampu Movement Area Guidance Sign (MAGS) di Bandar Udara Internasional I Gusti Ngurah Rai - Bali - Gautami, Nesya Livia Aura; Bunahri, Rifqi Raza; Nugrahayani, Tiara; Kona, Musri (Politeknik Penerbangan Jayapura, 2023)
The Movement Area Guidance Sign (MAGS) is a sign to provide information to the pilot in directing the movement of the aircraft during take-off, landing and taxiing (the road to the apron) efficiently and safely whose electrical power is supplied by a Constant Current Regulator (CCR). where the supply has a constant current and the network system is installed in series so that each lamp has the same brightness intensity. Bali's I Gusti Ngurah Rai International Airport is equipped with an Airfield Lightning System facility, a visual landing aid, one of which is the Movement Area Guidance Sign (MAGS) or better known as the Taxiway Guidance Sign. The MAGS lights at I Gusti Ngurah Rai International Airport Bali have 2 types of lights used, namely, 33 fluorescent type lights and 6 LED type boxes so that the total number of MAGS lights at the airport is 39 MAGS boxes. This research uses this type of research. qualitatively so that the analysis and calculation results show that LED lights are 57.94% more efficient than fluorescent TL lights at MAGS International Airport I Gusti Ngurah Rai. This is caused by the amount of power used by the lamp. In terms of quality, you may get more bang for your buck than your initial investment in MAGS LED lights. This is because LED lamps have a lifespan 3 times longer than fluorescent lamps and are brighter.